Caracterização do locus Fhos e sua participação na morte celular programada do intestino médio larval de Drosophila melanogaster - BENZE JÚNIOR, Roosevelt Antonio (2014)
Throughout metazoans physiological or programmed cell death (PCD), in its different fashion, apoptotic, autophagic and necrotic, plays a central role in maintaining homeostasis. Several diseases are associated with the misregulation of PCD, such as degenerative and autoimmune diseases as well as cancer. Several components of the PCD machinery were evolutionarily conserved even in such distinct organisms as insect and humans. In addition to these similarities, the variety of experimental tools available make Drosophila a powerfull for the characterization of new cell death-related genetic functions. Our group has used the PCD of larval salivary glands as an experimental model to study physiological cell death processes during Drosophila’s development. The PCD in larval salivary glands is regulated by ecdysone (steroid Hormone). Despite the extensive knowledge of the transcriptional cascade triggered by ecdysone, how, this systemic signal present in the hemolymph, ultimately promotes tissue and stage specific responses it is still unclear. To answer this question, we have carried out a genetic screen to identify new genes associated with regulation and execution of salivary gland PCD. In such screen we have identified a mutation mapped on the the Fhos locus which cause a cell death defective phenotype, the persistence of salivary glands. The genetic and functional characterization of the locus have shown that its function is essential for the proper PCD of salivary glands. The Fhos locus encodes proteins that share high similarity to the Formin family of proteins which have been shown to play a role in active cytoskeleton remodeling in distinct biological processes. In this work, we have performed the transcriptional analysis of one of the isoforms encoded by the Fhos locus, the Fhos-C isoform, that showed that this isoform is probably the fusion between Fhos and a flanking gene called “desert”. The trasncriptional analysis also revealed that the Fhos-C is diferentially expressed during development in lower levels. We have also started functional analysis of the Fhos locus using transgenic lines aiming to evaluate the potential function of it in the PCD of the larval midgut that is also eliminated by PCD during development. After determining the transcriptional profile of the biologicaly active isoform in the midgut (FhosB) we carried out overexpression and knockdown assays of this particular isoform. Taken together, our results reveal that the isoform-C is not active in the PCD during insect metamorphosis. Either, overexpression or knockdown of the isoform Fhos-B did not produced any relevant phenotype differently of the drastic one seen in salivary glands.